Fluorite particles as a novel calcite recovery depressant in scheelite flotation using Pb-BHA complexes as collectors. (1st March 2019) - Wang, Ruolin; Wei, Zhao; Han, Haisheng; Sun, Wei; Hu, Yuehua; Wang, Jianjun; Wang, Li; Liu, Hang; Yang, Yue; Zhang, Chenyang; He, Jianyong
Highlights: Surface transformation occurred on calcite and fluorite surface. Surface transformation may be beneficial to the flotation separation. A fluorite film formed on calcite surface in presence of fluorite particles. Fine fluorite particles are better than fluoride ion. Fluorite film prevents the adsorption of Pb-BHA complexes. Abstract: Lead complexes of benzohydroxamic acid (Pb-BHA complexes) have been successfully applied to the industrial separation of scheelite from calcite and fluorite minerals. However, the separation of scheelite from calcite using Pb-BHA complexes in the absence of fluorite is difficult. In flotation tests, both sodium fluoride and fluorite particles have been shown to depress calcite but not scheelite. Therefore, fluoride ions from the dissolved fluorite particles play an important role in the flotation separation of scheelite from calcite. In the current study, the results of zeta potential analysis confirmed that fluoride ions are strongly adsorbed on calcite surfaces and that the point of zero charge for calcite shifts to that of fluorite. X-ray photoelectron spectroscopy and atomic force microscopy analyses clearly indicated that the fluoride ions are adsorbed on the calcite surface to form a fluorite film. Thus, this type of surface transformation shows promise as a strategy for the flotation separation of semi-soluble minerals.